2021
DOI: 10.1093/schbul/sbab010
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Augmentation for Patients With Early-Phase Schizophrenia-Spectrum Disorders: A Double-Blind, Randomized Placebo-Controlled Trial

Abstract: Schizophrenia-spectrum disorders (SSD) are associated with increased inflammatory markers, both in brain and periphery. Augmentation with drugs that lower this pro-inflammatory status may improve clinical presentation. Simvastatin crosses the blood-brain barrier, has anti- inflammatory and neuroprotective effects and reduces metabolic syndrome. In this study, we investigated if 12 months of simvastatin augmentation can improve symptoms and cognition in patients with early SSD. This double-blind placebo-control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 41 publications
4
37
1
Order By: Relevance
“…A trial of Pravastatin augmentation of TAU did not show any significant benefit in outcomes except for a significant decrease in the PANSS positive symptoms score at 6 weeks; however, this was not seen at the 12-week study endpoint ( Vincenzi et al, 2014 ). Simvastatin augmentation of TAU resulted in lower total PANSS scores in the Simvastatin group at 6 and 24 months; however, there were no significant difference at pre-defined end point of 12 months ( Sommer et al, 2021 ). A trial of Pioglitazone as an adjunct to Risperidone showed a significant reduction in negative subscale and total PANSS at 8 weeks in the Pioglitazone group compared to placebo ( Iranpour et al, 2016 ).…”
Section: Resultsmentioning
confidence: 88%
“…A trial of Pravastatin augmentation of TAU did not show any significant benefit in outcomes except for a significant decrease in the PANSS positive symptoms score at 6 weeks; however, this was not seen at the 12-week study endpoint ( Vincenzi et al, 2014 ). Simvastatin augmentation of TAU resulted in lower total PANSS scores in the Simvastatin group at 6 and 24 months; however, there were no significant difference at pre-defined end point of 12 months ( Sommer et al, 2021 ). A trial of Pioglitazone as an adjunct to Risperidone showed a significant reduction in negative subscale and total PANSS at 8 weeks in the Pioglitazone group compared to placebo ( Iranpour et al, 2016 ).…”
Section: Resultsmentioning
confidence: 88%
“…Samples and data analysed in the present study were collected as part of the clinical trial of simvastatin supplementation in schizophrenia (ClinicalTrials.gov identifier: NCT01999309 [ 17 , 18 ]). The study population consisted of 119 participants between 18 and 50 years old diagnosed with schizophrenia spectrum disorder using the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV) [ 19 ] guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…65,94,[187][188][189][190][191] In schizophrenia and psychosis, evidence is also restricted; a few, relatively small RCTs have tested anti-inflammatory drugs, including the tetracyclic minocycline, the statin simvastatin, nonsteroidal anti-inflammatory drugs such as aspirin or celecoxib, and the anti-IL-6R monoclonal antibody tocilizumab, as adjuncts to standard antipsychotic medication. [192][193][194][195][196][197][198][199][200][201] As summarized in a recent meta-analysis, these RCTs reported promising results for some drugs, particularly regarding negative symptoms of schizophrenia that are usually difficult to treat. [192][193][194][195][196][197] There were also notable negative findings, however, warranting replication in larger RCTs that should selectively recruit patients with early psychosis and high baseline levels of inflammation.…”
Section: Early-life Immuno-metabolic Alterations As Potential Prevent...mentioning
confidence: 96%
“…[192][193][194][195][196][197] There were also notable negative findings, however, warranting replication in larger RCTs that should selectively recruit patients with early psychosis and high baseline levels of inflammation. [198][199][200][201][202] Overall, the evidence from RCTs of anti-inflammatory treatments for depression and psychosis makes apparent that these treatments are unlikely to provide a uniform treatment strategy for all patients. This is not a surprise, as immunometabolic alterations are not universally present in all cases of depression or psychosis.…”
Section: Early-life Immuno-metabolic Alterations As Potential Prevent...mentioning
confidence: 99%